IMPLEMENTASI PROGRAM PENERTIBAN PEMAKAIAN TENAGA LISTRIK (P2TL) PT PLN (PERSERO) DISTRIBUSI JAWA TENGAH DAN D.I.YOGYAKARTA DI KOTA SEMARANG - Karina Nindarwanti; Dyah Lituhayu; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Electricity is the very important life needs in supporting daily activities. Therefore, as the provider of national electricity services, PLN strive to fulfil the needs maximally. One of the cause of the problems is the high level of losses because of both technical and non-technical factors. The aims of this research are to describe the implementation of Power Consumption Control Program (P2TL) in Semarang City, the problems and obstructions occurred in the program implementation, and the solution for the problems. The research type applied was phenomenology. The research design used in this research was the qualitative research with inductive approach. The phenomena or symptoms in this research were the implementation process of P2TL, consemer participation in the implementation of P2TL, Human Resources availability, implementor understanding and legal assurance. The phenomena and symptoms were obtained besed on the observation and field survey results. In accordance with the research result, in general the imlpementation of Power Consumption Control program (P2TL) in Semarang City has not run well and maximally. It is based on the research and findings in the field that it as faound some infelicities in the implementation process implementor do not have clear job description and organization, and involvd the third party in the organization structure. Then, in the legal assurance regarding the sanctions imposed, there was not transparency between the implementor and policy receptor (consumers/people).